EXPRESSION OF TRANSFORMING GROWTH FACTOR ALPHA BAMHI AND RSAI GENE VARIANTS ASSOCIATED WITH NON-SYNDROMIC CLEFT PALATE OF INDONESIAN SUBJECTS USING POLYMERASE CHAIN REACTION METHOD - Melani Maskoen, Ani; L Nasroen, Saskia; Nanda Fauziah, Prima; Setiawan Soeria Soemantri, Eky; A Gani, Basri (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: This study aimed to detect and analyze transforming growth factor alpha (TGFA) BamHI and RsaI gene variants which associated with the risk factor of non-syndromic cleft palate only (NS CPO) of Indonesian subject. Methods: This was case-control study using samples from 32 NS CPO subjects and 28 control subjects. DNA was extracted from venous blood, and the TGFA gene was amplified using polymerase chain reaction technique, then digestion product from TaqI and RsaI restriction enzyme was evaluated. Statistical analysis to determine significant differences of gene variant frequency among NS CPO subject and control was Ï‡2. The odds ratio (OR) was used to determine a risk factor of NS CPO. Results: The study results showed that the TGFA BamHI gene variant was not identified in NS CPO among Indonesian but TGFA RsaI gene variant was identified. The frequency of TT/B1B1 homozygous mutant genotype was 80.0% in NS CPO subjects and 20.0% in control subjects (OR=3.857; 95% confidence interval=0.405â€“36.749). Conclusion: TGFA RsaI gene can be considered a risk factor of NS CPO compared TGFA BamH1 gene of Indonesian subjects.